Jimmie Johnson Collection - Ray City Community Library, Ray City Community Library (Ray City School, 1930)
Jimmie Johnson Collection, ca. 1930s. Ray City School. CA014-003: Ray City Community Library, 1936–ca. 1960 Series. Ray City Community Library Collection.
Jimmie Johnson Collection, ca. 1930s. 1 electronic record (PDF), 658 MB (690,855,400 bytes).
Keywords: Berrien County (Ga.); Ray City (Ga.); Ray City School; Vintage Textbooks; Schoolbooks